The Impact of The Free Nutritious Meal Program on The Transformation of The Learning Environment And Students' Social Interaction - Nur Baeni; Muh. Tahir Malik; Asri Asri (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study employed a qualitative research design with a phenomenological approach. The informants of the study consisted of students as the primary informants; the principal and teachers as the key informants; and parents and educational support staff as the supporting informants. Data collection techniques were conducted through interviews, observations, and documentation, while data analysis involved data reduction, data display, and conclusion drawing. The results of the study indicated that the implementation of MBG helped establish students' learning readiness, shape the regularity of school activities, and create a more conducive learning atmosphere. The MBG program also had an impact on increasing students' learning focus through enhanced concentration, learning stamina, and student motivation. Furthermore, MBG provided a social impact in the form of increased social interaction, togetherness, and student discipline in school activities. From an economic perspective, this program helped reduce a portion of the students' families' daily consumption expenditures. Consequently, the Free Nutritious Meal Program does not only function as a nutritional fulfillment program but also contributes to the formation of the learning environment, social behavior, and the welfare of the students' families.